Lithium slag slurry for concrete and application thereof
By preparing modified lithium slurry, the problems of high water demand and large changes in admixture dosage caused by high SO3 and alkali content and porous structure in the concrete are solved, and the workingability and slump retention of the concrete are improved, thereby achieving high value of lithium slag.
Patent Information
- Application Number
- CN202411944483.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
When existing lithium slag is used as a blend of concrete, the admixture dosage changes greatly due to high SO3 and alkali content and porous structure, which affects the performance of the concrete.
A lithium slurry for concrete is used, which consists of modified lithium slag, water, dispersant and stabilizer. The modified lithium slag is treated by prepreg, acid dissolution treatment and water washing to reduce the SO3 and alkali content, and improve the workingability and slump retention of the concrete through polycarboxylic acid-based water reducing agent and stabilizer.
By homogenizing the composition of lithium slag, the water demand is reduced, the workingability and slump resistance of concrete are improved, and the high-energy-consuming drying and grinding process is avoided, and the high-value and large-scale utilization of lithium slag is achieved.
Smart Images

Figure BDA0005213313720000061 
Figure BDA0005213313720000071 
Figure BDA0005213313720000072
Abstract
Description
Technical Field
[0001] This invention relates to the field of concrete materials technology, and in particular to a lithium slag slurry for concrete and its application. Background Technology
[0002] Lithium slag is a byproduct of the lithium carbonate production process using the sulfuric acid method after high-temperature roasting of spodumene. Its main components are SiO2, Al2O3, and CaO. If not comprehensively utilized as a resource, it is considered solid waste and will cause secondary pollution. To meet the global demand for a low-carbon future, lithium, as a renewable energy source and the most promising material for continuous energy storage and energy storage equipment, is highly favored. Lithium production is projected to increase fivefold by 2050 compared to 2018. As one of the major strategic countries for lithium salts, my country is experiencing a significant increase in lithium slag emissions due to the expansion of the lithium salt application market and rapid growth in demand. At the current lithium extraction technology level, producing 1 ton of lithium product generates 8-10 tons of lithium slag. Large amounts of lithium slag are piled up in the open or used for landfills, occupying vast amounts of land and causing serious environmental damage. This also hinders the sustainable development of lithium salts as a clean energy source.
[0003] Currently, lithium slag is mainly used as a raw material for cement clinker and as an admixture in concrete. However, its application as a concrete admixture faces several challenges: 1. High SO3 content, reaching over 15%; 2. The moisture content of raw lithium slag is around 20%, and its porous structure leads to high energy consumption during drying and grinding to produce lithium slag powder; 3. Due to its porous structure, raw lithium slag has a high water requirement and strong adsorption of admixtures, resulting in significant increases in admixture dosage and substantial losses over time when used directly as an admixture. Adding lithium slag to concrete can improve its pore structure, reduce shrinkage and permeability, and increase its elastic modulus. However, the high moisture content, high water requirement, and low later-stage activity of lithium slag in cement concrete limit its application. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to provide a lithium slag slurry for concrete, so as to solve the problem that when lithium slag is used as an admixture in concrete, the high SO3 and alkali content and porous structure lead to large variations in the amount of admixtures in lithium slag-admixed concrete, which in turn affects the performance of concrete.
[0005] The technical solution adopted by the present invention to solve its technical problem is: a lithium slag slurry for concrete, which, by weight of 100 parts, is composed of the following components: 50 parts lithium slag, 35-60 parts water, 0.5-1 parts dispersant, and 0.1-0.5 parts stabilizer;
[0006] The lithium slag is a modified lithium slag, and the modification method is as follows:
[0007] S1: At room temperature, the undisturbed lithium slag is pre-impregnated with water or dilute acid solution to obtain pre-impregnated lithium slag; the undisturbed lithium slag is a solid waste generated after lithium extraction from spodumene using sulfuric acid, wherein the lithium content is ≥0.2% and SO3≤10%;
[0008] S2: At a temperature of 25℃~60℃, the pre-impregnated lithium slag is treated with acid leaching, and then solid-liquid separation is performed to obtain acid-leached slag and lithium-rich solution; the acid is a dilute sulfuric acid solution with a mass percentage concentration of 3%~10%;
[0009] S3: At room temperature, the acid leaching residue is washed with water, and then solid-liquid separation is performed to obtain modified lithium slag and dilute acid solution;
[0010] The dispersant is a polycarboxylate superplasticizer;
[0011] The stabilizer is one or a mixture of several of sodium dodecyl sulfonate, aluminum silicate, hydroxyethyl cellulose, or hydroxypropyl methyl cellulose.
[0012] Furthermore, the dilute acid solution obtained in S3 with a pH of 2 ≤ pH ≤ 5 is returned to S1 to pre-soak the undisturbed lithium slag.
[0013] Furthermore, in S1, the ratio of undisturbed lithium slag to dilute acid is 1:1, and the pre-soaking time is 1 hour.
[0014] Furthermore, the acid dissolution time of S2 is 3-8 hours, and the stirring rate is 2-6 r / min.
[0015] Furthermore, the solid-liquid separation method of S3 is pressure filtration, vacuum filtration, or centrifugation.
[0016] Furthermore, the undisturbed lithium slag is a byproduct of the process of producing lithium carbonate using the sulfuric acid method after high-temperature roasting of spodumene, wherein the mass fractions of SiO2, Al2O3 and Fe2O3 are ≥60%, the mass fraction of SO3 is ≤10%, and the mass fraction of Li2O is ≥0.25%.
[0017] Furthermore, the stabilizer is made by mixing sodium dodecyl sulfonate, aluminum silicate, and hydroxypropyl methylcellulose in a mass ratio of 3:5:2.
[0018] Furthermore, the polycarboxylate superplasticizer has a solids content of 9% to 13%.
[0019] Furthermore, the lithium slag slurry for concrete is prepared by mixing modified lithium slag, water and dispersant evenly, stirring for 20-40 minutes, adding stabilizer and stirring for another 20-40 minutes to obtain the lithium slag slurry for concrete.
[0020] The above-described application of lithium slag slurry in concrete, wherein the amount of lithium slag slurry used is 15% to 30% of the cement content in the concrete after the lithium slag slurry has been folded and solidified.
[0021] The beneficial effects of the present invention are: by preparing lithium slag into lithium slag slurry and homogenizing the lithium slag, the present invention avoids the quality risks caused by the uneven distribution of harmful substances in lithium slag, solves the problem of high water demand caused by the porous structure in lithium slag, and improves the workability and slump retention of the prepared concrete.
[0022] This process avoids the energy consumption associated with drying and grinding lithium slag, enabling the high-value utilization and large-scale application of lithium slag. The lithium-rich solution obtained during the modification of undisturbed lithium slag can be used to prepare lithium carbonate. The lithium slag slurry prepared can increase the dosage of undisturbed lithium slag in concrete by 15% to 20%. Detailed Implementation
[0023] The present invention will be further described below with reference to embodiments.
[0024] Example 1:
[0025] Preparation of modified lithium slag:
[0026] S1: At room temperature, the undisturbed lithium slag was pre-soaked in a dilute sulfuric acid solution with pH=4 at a ratio of 1:1 for 1 hour to obtain pre-soaked lithium slag; the undisturbed lithium slag came from a lithium extraction enterprise in Mianyang, Sichuan, and its SiO2, Al2O3 and Fe2O3 contents were 73%, SO3 content was 7.6%, Li2O content was 0.3%, and alkali content (Na2O+0.658K2O) was 1.0%;
[0027] S2: At a temperature of 40±2℃, the pre-impregnated lithium slag is treated with acid leaching. The pre-impregnated lithium slag and 5% dilute sulfuric acid are mixed in a ratio of 1:5 and placed in a heatable stirrer at a stirring rate of 3r / min. After leaching for 5 hours, solid-liquid separation is carried out by suction filtration to obtain acid-leached slag and lithium-rich solution.
[0028] S3: At room temperature, the acid leaching residue is washed twice with water. The final diluted acid solution obtained from the water washing has a pH value of 4. Then, solid-liquid separation is performed to obtain modified lithium slag and dilute acid solution.
[0029] The modified lithium slag has an SO3 content of 4.8%, a Li2O content of 0.1%, and an alkali content (Na2O + 0.658K2O) of 0.2%.
[0030] Preparation of stabilizers:
[0031] Weigh 300g sodium dodecyl sulfonate, 500g aluminum silicate, and 200g hydroxypropyl methylcellulose, and mix them evenly.
[0032] The dispersant is a polycarboxylate superplasticizer with a solid content of 10%.
[0033] A lithium slag slurry for concrete, by weight, comprises the following raw materials: 100 parts modified lithium slag, 98.5 parts water, 1 part dispersant, and 0.5 parts prepared stabilizer. The modified lithium slag, water, and dispersant are mixed evenly and stirred for 30 minutes. Then, the stabilizer is added and stirred for another 30 minutes to obtain the lithium slag slurry for concrete. The resulting lithium slag slurry has a water content of 50% and a dry basis content of 50%.
[0034] The concrete mix design is shown in Table 1. In this embodiment, lithium slag slurry is used to replace part of the cement. Specifically, the replacement amount is 30% of the cement usage by the weight of the lithium slag slurry after folding. That is, 216 kg of lithium slag slurry is used to replace 108 kg of cement and 108 kg of water.
[0035] Table 1 Concrete mix proportions (kg / m³) 3 )
[0036] Serial Number Water consumption cement Lithium slag slurry Manufactured sand gravel Water reducing agent Water-reducing agent dosage Sand ratio Water-to-glue ratio density Blank group 165 360 0 822 1047 6.48 1.8% 0.44 0.46 2400 Example 1 57 252 216 822 1047 6.48 1.8% 0.44 0.46 2400 Example 2 57 252 216 822 1047 6.48 1.8% 0.44 0.46 2400 Example 3 93 252 180 822 1047 6.48 1.8% 0.44 0.46 2400 Comparative Example 1 57 252 216 822 1047 10.08 2.8% 0.44 0.46 2400 Comparative Example 2 57 252 216 822 1047 9.36 2.6% 0.44 0.46 2400 Comparative Example 3 57 252 216 822 1047 9.72 2.7% 0.44 0.46 2400 Comparative Example 4 57 252 216 822 1047 10.80 3.0% 0.44 0.46 2400 Comparative Example 5 57 252 216 822 1047 6.48 1.8% 0.44 0.46 2400 Comparative Example 6 93 252 180 822 1047 7.20 2.0% 0.44 0.46 2400
[0037] Example 2:
[0038] The preparation of modified lithium slag and stabilizer is the same as in Example 1.
[0039] A lithium slag slurry for concrete, by weight, comprises the following raw materials: 100 parts modified lithium slag, 98 parts water, 1 part dispersant, and 1 part prepared stabilizer. The modified lithium slag, water, and dispersant are mixed evenly and stirred for 30 minutes. Then, the stabilizer is added and stirred for another 30 minutes to obtain the lithium slag slurry for concrete. The resulting lithium slag slurry has a water content of 50% and a dry basis content of 50%.
[0040] The concrete mix design is shown in Table 1. In this embodiment, lithium slag slurry is used to replace part of the cement. Specifically, the replacement amount is 30% of the cement amount after the lithium slag slurry is folded and solidified. That is, 216 kg of lithium slag slurry is used to replace 108 kg of cement and 108 kg of water.
[0041] Example 3:
[0042] The preparation of modified lithium slag and stabilizer is the same as in Example 1.
[0043] A lithium slag slurry for concrete, by weight, comprises the following raw materials: 100 parts modified lithium slag, 64 parts water, 2 parts dispersant, and 0.6 parts prepared stabilizer. The modified lithium slag, water, and dispersant are mixed evenly and stirred for 30 minutes. Then, the stabilizer is added and stirred for another 30 minutes to obtain the lithium slag slurry for concrete. The resulting lithium slag slurry has a water content of 40% and a dry basis content of 60%.
[0044] The concrete mix design is shown in Table 1. In this embodiment, lithium slag slurry is used to replace part of the cement. Specifically, the replacement amount is 30% of the cement amount after the lithium slag slurry is folded and solidified. That is, 180 kg of lithium slag slurry is used to replace 108 kg of cement and 72 kg of water.
[0045] Comparative Example 1:
[0046] Preparation of modified lithium slag: (The dissolution temperature in step S2 is 20±2℃, and the rest is the same as in Example 1)
[0047] S1: At room temperature, the undisturbed lithium slag was pre-soaked in a dilute sulfuric acid solution with pH=4 at a ratio of 1:1 for 1 hour to obtain pre-soaked lithium slag; the undisturbed lithium slag came from a lithium extraction enterprise in Mianyang, Sichuan, and its SiO2, Al2O3 and Fe2O3 contents were 73%, SO3 content was 7.6%, Li2O content was 0.3%, and alkali content (Na2O+0.658K2O) was 1.0%;
[0048] S2: At a temperature of 20±2℃, the pre-impregnated lithium slag is treated with acid leaching. The pre-impregnated lithium slag and 5% dilute sulfuric acid are mixed in a ratio of 1:5 and placed in a heatable stirrer at a stirring rate of 3r / min. After leaching for 5 hours, solid-liquid separation is carried out by suction filtration to obtain acid-leached slag and lithium-rich solution.
[0049] S3: At room temperature, the acid leaching residue is washed twice with water. The final diluted acid solution obtained from the water washing has a pH value of 4. Then, solid-liquid separation is performed to obtain modified lithium slag and dilute acid solution.
[0050] The modified lithium slag has an SO3 content of 7.0%, a Li2O content of 0.2%, and an alkali content (Na2O + 0.658K2O) of 0.8%.
[0051] Preparation of stabilizers:
[0052] Weigh 300g sodium dodecyl sulfonate, 500g aluminum silicate, and 200g hydroxypropyl methylcellulose, and mix them evenly.
[0053] The dispersant is a polycarboxylate superplasticizer with a solid content of 10%.
[0054] A lithium slag slurry for concrete, by weight, comprises the following raw materials: 100 parts modified lithium slag, 98.5 parts water, 1 part dispersant, and 0.5 parts prepared stabilizer. The modified lithium slag, water, and dispersant are mixed evenly and stirred for 30 minutes. Then, the stabilizer is added and stirred for another 30 minutes to obtain the lithium slag slurry for concrete. The resulting lithium slag slurry has a water content of 50% and a dry basis content of 50%.
[0055] The concrete mix design is shown in Table 1. In this embodiment, lithium slag slurry is used to replace part of the cement. Specifically, the replacement amount is 30% of the cement usage by the weight of the lithium slag slurry after folding. That is, 216 kg of lithium slag slurry is used to replace 108 kg of cement and 108 kg of water.
[0056] Comparative Example 2:
[0057] Preparation of modified lithium slag: (The concentration of dilute sulfuric acid in step S2 is 15%, and other steps are the same as in Example 1)
[0058] S1: At room temperature, the undisturbed lithium slag was pre-soaked in a dilute sulfuric acid solution with pH=4 at a ratio of 1:1 for 1 hour to obtain pre-soaked lithium slag; the undisturbed lithium slag came from a lithium extraction enterprise in Mianyang, Sichuan, and its SiO2, Al2O3 and Fe2O3 contents were 73%, SO3 content was 7.6%, Li2O content was 0.3%, and alkali content (Na2O+0.658K2O) was 1.0%;
[0059] S2: At a temperature of 40±2℃, the pre-impregnated lithium slag is treated with acid leaching. The pre-impregnated lithium slag and 15% dilute sulfuric acid are mixed in a ratio of 1:5 and placed in a heatable stirrer at a stirring rate of 3r / min. After leaching for 5 hours, solid-liquid separation is carried out by suction filtration to obtain acid-leached slag and lithium-rich solution.
[0060] S3: At room temperature, the acid leaching residue is washed twice with water. The final diluted acid solution obtained from the water washing has a pH value of 4. Then, solid-liquid separation is performed to obtain modified lithium slag and dilute acid solution.
[0061] The modified lithium slag has an SO3 content of 8.2%, a Li2O content of 0.1%, and an alkali content (Na2O + 0.658K2O) of 0.6%.
[0062] Preparation of stabilizers:
[0063] Weigh 300g sodium dodecyl sulfonate, 500g aluminum silicate, and 200g hydroxypropyl methylcellulose, and mix them evenly.
[0064] The dispersant is a polycarboxylate superplasticizer with a solid content of 10%.
[0065] A lithium slag slurry for concrete, by weight, comprises the following raw materials: 100 parts modified lithium slag, 98.5 parts water, 1 part dispersant, and 0.5 parts prepared stabilizer. The modified lithium slag, water, and dispersant are mixed evenly and stirred for 30 minutes. Then, the stabilizer is added and stirred for another 30 minutes to obtain the lithium slag slurry for concrete. The resulting lithium slag slurry has a water content of 50% and a dry basis content of 50%.
[0066] The concrete mix design is shown in Table 1. In this embodiment, lithium slag slurry is used to replace part of the cement. Specifically, the replacement amount is 30% of the cement usage by the weight of the lithium slag slurry after folding. That is, 216 kg of lithium slag slurry is used to replace 108 kg of cement and 108 kg of water.
[0067] Comparative Example 3:
[0068] Preparation of modified lithium slag: (Step S3 is omitted; all other steps are the same as in Example 1)
[0069] S1: At room temperature, the undisturbed lithium slag was pre-soaked in a dilute sulfuric acid solution with pH=4 at a ratio of 1:1 for 1 hour to obtain pre-soaked lithium slag; the undisturbed lithium slag came from a lithium extraction enterprise in Mianyang, Sichuan, and its SiO2, Al2O3 and Fe2O3 contents were 73%, SO3 content was 7.6%, Li2O content was 0.3%, and alkali content (Na2O+0.658K2O) was 1.0%;
[0070] S2: At a temperature of 40±2℃, the pre-impregnated lithium slag was treated with acid leaching. The pre-impregnated lithium slag and 5% dilute sulfuric acid were mixed in a ratio of 1:5 and placed in a heatable stirrer at a stirring rate of 3r / min. After leaching for 5 hours, solid-liquid separation was carried out by vacuum filtration to obtain modified lithium slag and lithium-rich solution.
[0071] The modified lithium slag has an SO3 content of 6.0%, a Li2O content of 0.1%, and an alkali content (Na2O + 0.658K2O) of 0.6%.
[0072] Preparation of stabilizers:
[0073] Weigh 300g sodium dodecyl sulfonate, 500g aluminum silicate, and 200g hydroxypropyl methylcellulose, and mix them evenly.
[0074] The dispersant is a polycarboxylate superplasticizer with a solid content of 10%.
[0075] A lithium slag slurry for concrete, by weight, comprises the following raw materials: 100 parts modified lithium slag, 98.5 parts water, 1 part dispersant, and 0.5 parts prepared stabilizer. The modified lithium slag, water, and dispersant are mixed evenly and stirred for 30 minutes. Then, the stabilizer is added and stirred for another 30 minutes to obtain the lithium slag slurry for concrete. The resulting lithium slag slurry has a water content of 50% and a dry basis content of 50%.
[0076] The concrete mix design is shown in Table 1. In this embodiment, lithium slag slurry is used to replace part of the cement. Specifically, the replacement amount is 30% of the cement usage by the weight of the lithium slag slurry after folding. That is, 216 kg of lithium slag slurry is used to replace 108 kg of cement and 108 kg of water.
[0077] Comparative Example 4: (The lithium slag is undisturbed lithium slag; all other aspects are the same as in Example 1)
[0078] A lithium slag slurry for concrete, by weight, comprises the following raw materials: 100 parts of undisturbed lithium slag, 98.5 parts of water, 1 part of dispersant, and 0.5 parts of prepared stabilizer. The undisturbed lithium slag, water, and dispersant are mixed evenly and stirred for 30 minutes. Then, the stabilizer is added and stirred for another 30 minutes to obtain the lithium slag slurry for concrete. The resulting lithium slag slurry has a water content of 50% and a dry basis content of 50%.
[0079] The concrete mix design is shown in Table 1. In this embodiment, lithium slag slurry is used to replace part of the cement. Specifically, the replacement amount is 30% of the cement amount after the lithium slag slurry is folded and solidified. That is, 216 kg of lithium slag slurry is used to replace 108 kg of cement and 108 kg of water.
[0080] Comparative Example 5: (No stabilizer used, otherwise the same as Example 2)
[0081] The preparation of modified lithium slag is the same as in Example 1.
[0082] A lithium slag slurry for concrete, by weight, comprises the following raw materials: 100 parts modified lithium slag, 99 parts water, and 1 part dispersant. The modified lithium slag, water, and dispersant are mixed evenly and stirred for 30 minutes. Then, a stabilizer is added and stirred for another 30 minutes to obtain the lithium slag slurry for concrete. The resulting lithium slag slurry has a water content of 50% and a dry basis content of 50%.
[0083] The concrete mix design is shown in Table 1. In this embodiment, lithium slag slurry is used to replace part of the cement. Specifically, the replacement amount is 30% of the cement amount after the lithium slag slurry is folded and solidified. That is, 216 kg of lithium slag slurry is used to replace 108 kg of cement and 108 kg of water.
[0084] Comparative Example 6: (No dispersant used, otherwise the same as Example 3)
[0085] The preparation of modified lithium slag is the same as in Example 1.
[0086] A lithium slag slurry for concrete, by weight, comprises the following raw materials: 100 parts modified lithium slag, 64 parts water, and 0.6 parts a prepared stabilizer. The modified lithium slag, water, and dispersant are mixed evenly and stirred for 30 minutes. Then, the stabilizer is added and stirred for another 30 minutes to obtain the lithium slag slurry for concrete. The resulting lithium slag slurry has a water content of 40% and a dry basis content of 60%.
[0087] The concrete mix design is shown in Table 1. In this embodiment, lithium slag slurry is used to replace part of the cement. Specifically, the replacement amount is 30% of the cement amount after the lithium slag slurry is folded and solidified. That is, 180 kg of lithium slag slurry is used to replace 108 kg of cement and 72 kg of water.
[0088] The sedimentation of the lithium slag slurry prepared in the examples and comparative examples was observed. The observation method was to put 80 mL of lithium slag slurry into a 100 mL graduated cylinder and let it stand for 8 hours, 16 hours, 24 hours, 48 hours and 72 hours, and observe the height of the supernatant. The observation results are shown in Table 2.
[0089] Concrete was prepared using lithium slag slurry prepared in the examples and comparative examples, and its initial workability, 1-hour, 2-hour and 3-hour workability, 7-day mechanical properties and 28-day mechanical properties were tested. The test results are shown in Tables 3 and 4.
[0090] Table 2. Settling observation results of lithium slag slurry (mL)
[0091]
[0092]
[0093] Table 3 Concrete Test Results - Workability (1) Slump, Spread Unit: mm
[0094]
[0095] Table 4. Concrete Test Results - Mechanical Properties (2)
[0096]
[0097]
[0098] Analyzing the data in the table above, we can see that:
[0099] 1) When the amount of lithium slag slurry used to replace cement in concrete prepared in Examples 1-3 is 30%wt, the amount of admixture in the fresh concrete does not change much, and the workability is better than that of the blank group. In terms of hardened concrete, the 7-day strength is about 68% of that of the blank group, the 28-day strength is about 95% of that of the blank group, and the 60-day strength is about 100% of that of the blank group, showing good pozzolanic activity.
[0100] 2) The performance comparison analysis of concrete prepared by replacing cement with lithium slag slurry in concrete prepared in Example 1 and Comparative Examples 1-4 shows that the modified lithium slag has a significant improvement in the admixture dosage and workability retention of fresh concrete compared with the original lithium slag or other modified lithium slag. After the original lithium slag is treated by the modification method, the alkali content and SO3 content in the lithium slag are significantly reduced, which reduces the impact on admixtures.
[0101] 3) By comparing the sedimentation of the lithium slag slurry for concrete prepared in Example 2 and Comparative Example 2, it was found that the stabilizer significantly improved the stability of the lithium slag slurry suspension and reduced the sedimentation of the lithium slag slurry under static conditions, thus reducing the mixing cost for subsequent use.
Claims
1. A lithium slag slurry for concrete, characterized in that: The composition is composed of the following components based on 100 parts by weight: 50 parts of lithium slag, 35-60 parts of water, 0.5-1 part of dispersant, and 0.1-0.5 part of stabilizer; The lithium slag is modified lithium slag, and the modification method thereof is as follows: S1: pre-impregnating the original lithium slag with water or a dilute acid solution at room temperature to obtain pre-impregnated lithium slag; the original lithium slag is solid waste generated after spodumene is subjected to a lithium extraction process by sulfuric acid, wherein the lithium content is ≥0.2% and SO3 ≤10%; S2: At a temperature of 25° C. to 60° C., acid dissolution treatment is performed on the pre-leached lithium slag, followed by solid-liquid separation to obtain acid-dissolved slag and a lithium-rich solution; the acid is a dilute sulfuric acid solution having a mass percentage concentration of 3% to 10%; S3: at room temperature, washing the acid-dissolved slag with water, and then performing solid-liquid separation to obtain modified lithium slag and a dilute acid solution; The dispersant is a polycarboxylic acid water reducer; The stabilizer is one or a mixture of sodium dodecyl sulfate, aluminum silicate, hydroxyethyl cellulose or hydroxypropyl methyl cellulose.
2. The lithium slag slurry for concrete according to claim 1, characterized in that: The dilute acid solution 2≤pH≤5 obtained in S3 is returned to S1 to pre-soak the original lithium slag.
3. The lithium slag slurry for concrete according to claim 2, characterized in that: In the S1, the ratio of original lithium slag to dilute acid solution is 1:1, and the pre-immersion time is 1 hour.
4. The lithium slag slurry for concrete according to claim 1, characterized in that: The acid dissolution time of S2 is 3 to 8 hours, and the stirring rate is 2 to 6 r / min.
5. The lithium slag slurry for concrete according to claim 1, characterized in that: The method for solid-liquid separation of S3 is filter pressing, suction filtration or centrifugation.
6. The lithium slag slurry for concrete according to claim 1, characterized in that: The original lithium slag is a byproduct of the process of producing lithium carbonate by sulfuric acid method after high-temperature roasting of spodumene, wherein the mass fraction of SiO2, Al2O3 and Fe2O3 is ≥60%, the mass fraction of SO3 is ≤10%, and the mass fraction of Li2O is ≥0.25%.
7. The lithium slag slurry for concrete according to claim 1, characterized in that: The stabilizer is prepared by mixing sodium dodecyl sulfate, aluminum silicate and hydroxypropyl methylcellulose in a mass ratio of 3:5:
2.
8. The lithium slag slurry for concrete according to claim 1, characterized in that: The solid content of the polycarboxylic acid water reducing agent is 9% to 13%.
9. The lithium slag slurry for concrete according to claim 1, characterized in that: The lithium slag slurry for concrete is prepared in the following manner: the modified lithium slag, water and dispersant are uniformly mixed, stirred for 20 to 40 minutes, and then a stabilizer is added and stirred for 20 to 40 minutes to obtain the lithium slag slurry for concrete.
10. The use of the lithium slag slurry for concrete according to claim 1 in concrete, characterized in that: The amount of lithium slag slurry used in concrete is such that the weight of the lithium slag slurry after solidification accounts for 15% to 30% of the amount of cement used in concrete.
Citation Information
Cited By
Comprehensive recovery method of lithium slag
CN120714773A